Employee Competence Development Strategy in The Future Organizational Transformation: an Analytical Approach Hierarchy Process - Ike Trisnawati; Anggraini Sukmawati; Yunus Triyonggo (LP2M IAIN Palopo, 2026)
Organizational changes marked by bureaucratic simplification have necessitated improving team member competency to achieve organizational goals. This study aims to determine strategic priorities in competency development decision-making. The study used the Analytical Hierarchy Process (AHP) method, which used Microsoft Excel to analyze the structure and main strategic alternatives—the analysis was based on primary data from interviews with 11 expert sources. The study results indicate that improving team member competency is the most crucial strategy in improving the organizational performance of the Ministry of Maritime Affairs and Fisheries (KKP), with strengthening the ASN education and training program as an integral part of the strategy. The most recommended strategic alternative is to build a competency-based education and training system for KKP ASN and the Functional Official Competency Certification. The results also indicate that leadership is the most important factor in ensuring the strategy for improving organizational competency. Therefore, the leadership quality of the Head of BBPPSDM KP is considered the most critical and influential actor in improving KKP organizational competency. Developing competency development policies and programs tailored to the needs that influence the career development of KKP functional officials is a primary goal that KKP must achieve. The managerial implications of this research are that public organizations must implement competency-based education and training and competency certification for functional officials. Leadership also plays a crucial role in strategic organizational management, empowering and directing organizational resources to achieve organizational goals effectively and efficiently.